2018
DOI: 10.1038/s41598-018-33729-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Bright Near-Infrared Perovskite Light-Emitting Diodes with Reduced Efficiency Roll-off

Abstract: Herein, an insulating biopolymer is exploited to guide the controlled formation of micro/nano-structure and physical confinement of α-δ mixed phase crystalline grains of formamidinium lead iodide (FAPbI3) perovskite, functioning as charge carrier concentrators and ensuring improved radiative recombination and photoluminescence quantum yield (PLQY). This composite material is used to build highly efficient near-infrared (NIR) FAPbI3 Perovskite light-emitting diodes (PeLEDs) that exhibit a high radiance of 206.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Furthermore, stable morphology of NC film or stable NC distribution in NC film is expected to be able to relieve efficiency roll-off. This is in agreement with some reports [13,40] on embedding perovskite in a matrix, in which the perovskite NCs or pArticles were fixed in the matrix and morphologies of the films are more stable during operation.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, stable morphology of NC film or stable NC distribution in NC film is expected to be able to relieve efficiency roll-off. This is in agreement with some reports [13,40] on embedding perovskite in a matrix, in which the perovskite NCs or pArticles were fixed in the matrix and morphologies of the films are more stable during operation.…”
Section: Resultssupporting
confidence: 93%
“…The intense PL emission band of 10MAPbI 3 -5S peaks at 795 nm, and it is slightly blue, shifting to 790 nm for 5MAPbI 3 -5S. The emission band position and intensities are in line with what was previously reported for these composites, and suggests good optoelectronic properties for the perovskite component of the ink [25].…”
Section: Resultssupporting
confidence: 84%
“…The addition of starch helped the formation of an α-δ mixed phase that can improve the radiative bimolecular recombination and circumvent losses at the interface between the emissive layer and the hole/electron-transporting layer; the improved substrate coverage of the perovskite film can inhibit current leakage and modulate the dielectric landscape, so that the light-outcoupling efficiency can be increased. 160 Many reports have demonstrated that the photophysical properties of perovskite materials can be modulated by changing the halide composition. In 2017, Xiao et al proposed that long-chain ammonium halides can act as surfactants that terminate the grain growth of 3D perovskite in the perovskite solutions during the film-forming process, producing small-grain-sized, ultrasmooth, pinhole-free, and compact perovskite films.…”
Section: D Perovskite Materialsmentioning
confidence: 99%